2018
DOI: 10.1038/s41421-018-0056-8
|View full text |Cite
|
Sign up to set email alerts
|

Four putative SWI2/SNF2 chromatin remodelers have dual roles in regulating DNA methylation in Arabidopsis

Abstract: DNA methylation is a conserved epigenetic mark that is critical for many biological processes in plants and mammals. In Arabidopsis, the antagonistic activities of RNA-directed DNA methylation (RdDM) and ROS1-dependent active DNA demethylation are key for the dynamic regulation of locus-specific DNA methylation. However, the molecular factors that coordinate RdDM and active demethylation are largely unknown. Here we report that CLSY4 and its three paralogous SWI2/SNF2-type chromatin-remodeling proteins functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 44 publications
3
17
0
Order By: Relevance
“…ROS1 is involved in establishing boundaries between TEs and genes at thousands of loci by preventing the spread of DNA methylation and DNA hypermethylation as it counteracts RdDM through a postulated mechanism based on the ability of ROS1 to demethylate its own promoter from RdDM hypermethylation (Zhang et al ., ). Recently, in addition to its role in the generation of 24‐nucleotide siRNAs (Zhou et al ., ), CLSY4 was found to function in DNA demethylation in the same genetic pathway of the ROS1 family (Yang et al ., ).…”
Section: Maintenance and Removal Of Dna Methylationmentioning
confidence: 97%
“…ROS1 is involved in establishing boundaries between TEs and genes at thousands of loci by preventing the spread of DNA methylation and DNA hypermethylation as it counteracts RdDM through a postulated mechanism based on the ability of ROS1 to demethylate its own promoter from RdDM hypermethylation (Zhang et al ., ). Recently, in addition to its role in the generation of 24‐nucleotide siRNAs (Zhou et al ., ), CLSY4 was found to function in DNA demethylation in the same genetic pathway of the ROS1 family (Yang et al ., ).…”
Section: Maintenance and Removal Of Dna Methylationmentioning
confidence: 97%
“…Pol IV activity depends on a family of four CLSY putative chromatin remodeling proteins (Greenberg et al, 2013;Smith et al, 2007;Zhou et al, 2018). Simultaneous loss of CLSY1 and CLSY2 has the same effect as loss of SHH1, whereas CLSY3 and CLSY4 mediate RdDM at a largely distinct set of loci (Yang et al, 2018;Zhou et al, 2018). Mutations of SHH1 and CLSY1/2 preferentially reduce mCHH and sRNA at DRM TEs and increase mCHH at CMT TEs (Figure 3C).…”
Section: Rddm Is Recruited To Cmt Tes Independently Of Shh1mentioning
confidence: 99%
“…Mass spectrometry found that CLASSY proteins, a subfamily of SWI2/SNF2-like ATPases related to chromatin remodelers, copurify with the Pol IV complex in A. thaliana and maize [36,62]. The biochemical activity of CLSY proteins has not been elucidated, but genetic screens have isolated clsy mutations that disrupt gene silencing in both these plant species [63][64][65]. The four A. thaliana proteins, CLSY1 through CLSY4, facilitate the association of Pol IV at about 90% of loci that give rise to 24 nt siRNAs [66].…”
Section: Pol IV and Pol V Non-coding Transcripts Guide De Novo Dna Mementioning
confidence: 99%